The influence of educational level and oral hygiene behaviours on DMFT index and CPITN index in an adult Italian population: an epidemiological study. Issue 2 (16th July 2014) - Vano, M; Gennai, S; Karapetsa, D; Miceli, M; Giuca, MR; Gabriele, M; Graziani, F
Abstract: Objectives: To estimate the influence of educational level and oral hygiene behaviours on the prevalence and severity of dental caries and periodontal disease in an adult Italian population attending the Oral Hygiene department of a public Dental Clinic. Methods: Dental caries was diagnosed according to the World Health Organization criteria. The DMFT index (decayed, missing, filled tooth) was used to record the dental caries' experience. The periodontal status was assessed using the community periodontal index of treatment needs (CPITN). Questionnaires on educational level and oral hygiene behaviours were also collected. Results: A total of 350 patients were enrolled. The mean DMFT value reported was 4.37 ± 3.06, and higher values were observed for male patients ( P  <   0.05). Increased CPITN scores and DMFT values were significantly correlated with lower level of education ( P  <   0.05). Subjects of high educational status showed significantly better oral hygiene habits ( P  <   0.05). Conclusions: The oral health status, in terms of periodontal disease and dental caries, appears correlated with patients' educational level.